2013
DOI: 10.2174/0929867311320040006
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Sweat Testing For Drugs of Abuse: A Review

Abstract: Sweat is an alternative biological matrix useful to detect drugs of abuse intake. It is produced by eccrine and apocrine glands originating in the skin dermis and terminating in secretory canals that flow into the skin surface and hair follicles. Since many years it has been demonstrated that endogenous and exogenous chemicals are secreted in this biological sample hence its collection and analysis could show the past intake of xenobiotics. From the seventies the excretion of drugs of abuse has been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 94 publications
1
56
0
1
Order By: Relevance
“…Because of the lack of a simple methodology, the detection and quantification of skin metabolites has not been favored in the clinical setting, with the exception of the diagnosis of cystic fibrosis in infants (12 ). Several methods for collecting small amounts of skin excretions have been proposed (cotton swab, wipe, skinpatch, and syringe), but all of them involve major inconveniences (13 ). Therefore, it would be helpful to develop and implement analytical methods for sampling and analyzing skin excretions that circumvent chromatographic separations (14,15 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Because of the lack of a simple methodology, the detection and quantification of skin metabolites has not been favored in the clinical setting, with the exception of the diagnosis of cystic fibrosis in infants (12 ). Several methods for collecting small amounts of skin excretions have been proposed (cotton swab, wipe, skinpatch, and syringe), but all of them involve major inconveniences (13 ). Therefore, it would be helpful to develop and implement analytical methods for sampling and analyzing skin excretions that circumvent chromatographic separations (14,15 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%
“…The main disadvantages of this sampling technique are the potential influence of external contamination of the skin or the sweat patches and the unknown sample volume (rendering interpretation of a quantitative result challenging), as sweat production may vary in function of physical activity or ambient temperature. Given the limited potential of sweat analysis in the routine clinical lab, the interested reader is referred to other recent reviews 23,24 .…”
Section: Alternative Sampling Strategiesmentioning
confidence: 99%
“…Several applications of sweat testing have been described, including measurement of chloride ions as a biomarker of cystic fibrosis [142] and detection of drugs of abuse in forensic toxicology, roadside and workplace drug testing [143][144][145].…”
Section: Miscellaneous Matricesmentioning
confidence: 99%
“…Limitations of this sampling strategy are the potential influence of external contamination of the devices or the skin and the unknown collected volume, as sweat production may vary in function of ambient temperature or physical activity [145]. Delahunty et al suggested that sweat could potentially be used as an alternative for urine or plasma to estimate CYP1A2 activity.…”
Section: Miscellaneous Matricesmentioning
confidence: 99%